DEMANDA E OFERTA ENERGÉTICA: UMA PERSPECTIVA MUNDIAL E NACIONAL PARA O ETANOL - Schutz, Fernanda; Massuquetti, Angélica; Alves, Tiago Wickstrom (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This paper estimates the bilateral trade flows between the BRICs – Brazil, Russia, India and China – in the next decades. This study employs a gravity model based on a sample of 57 countries. Trade flows and a variety of other data were collected from 2000 to 2007 to enable the estimation of gravity equations that explain the international trade in this period. By using two different estimation methods – OLS and Tobit – a wide set of parameters was generated, with the aim to choose the most adequate equations for the estimations wanted. Finally, these two best parameter sets were arranged and applied on gravity equations, combined with the Goldman Sachs predictions, in order to obtain future estimations of bilateral trade flows between them in three time-scenarios: short term (2010), midterm (2020) and long term (2030). The results show that the ‘intra-BRICs’ trade flows will grow even more than the GDP of these countries, meaning an increase in the interdependence among these economies, contributing to maintain their economic growth.